2019
DOI: 10.3390/ijerph16091660
|View full text |Cite
|
Sign up to set email alerts
|

MRSA Point Prevalence among Health Care Workers in German Rehabilitation Centers: A Multi-Center, Cross-Sectional Study in a Non-Outbreak Setting

Abstract: People working in health care services have an increased risk of being infected with methicillin-resistant Staphylococcus aureus (MRSA), though little is known about the prevalence in rehabilitation centers. This cross-sectional study investigated the MRSA prevalence in employees from different rehabilitation centers and aimed to identify risk factors for MRSA transmission. We invited all staff (i.e., with and without patient contact from 22 participating rehabilitation centers; n = 2499) to participate. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Schubert et al reported that methicillin resistance was not related to diabetes, hospital admission, chronic respiratory disorder, or antibiotics consumption. But, contact with MRSA patients, and previous history of MRSA colonization were possible factors associated with high frequency of MRSA colonization [40].…”
Section: Discussionmentioning
confidence: 99%
“…Schubert et al reported that methicillin resistance was not related to diabetes, hospital admission, chronic respiratory disorder, or antibiotics consumption. But, contact with MRSA patients, and previous history of MRSA colonization were possible factors associated with high frequency of MRSA colonization [40].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been observed in German Rehabilitation Centers and the Netherlands where MRSA carriage in health-care workers in contact with livestock is higher than in other health-care workers, though the difference is not statistically significant. 39 , 40 The possible explanation may be due to the likelihood of animal-to-human transmission through kissing, licking, bathing, or other coordinated contacts with colonized animals.…”
Section: Discussionmentioning
confidence: 99%
“…We also evaluated both donors and recipients for MDROs (CRE, VRE, ESBL) in stool and MRSA in nasopharyngeal samples. The incidence of MDROs including MRSA among donors and recipients was 0.0%, lower than reported point prevalence rates of MRSA colonization among hospital-exposed patients in an urban, nonoutbreak setting [ 50 , 51 ].…”
Section: Resultsmentioning
confidence: 70%